Visual rhetoric in Michel Gondry's music videos: Antithesis and similarity in Deadweight. Issue 1 (1st January 2015) - Buckland, Warren
This article analyses the visual rhetoric of Michel Gondry's Deadweight (1997), a music video for Beck Hansen's song of the same name, and also considers the song's relation to Danny Boyle's film A Life Less Ordinary (1997). Two key structures are identified in the video: antithesis and similarity – which Gondry employs to visually illustrate the title of both Beck's song and Boyle's film.